Spatial-temporal and Factors Influencing the Distribution of Biodiversity: A Review - Girma Gizachew (ASEAN Journal of Science and Engineering, 2022)
Ecosystem health and the accomplishment of the Sustainable Development Goals require biodiversity. However, the causes of biodiversity loss, as well as regional differences in their repercussions, remain poorly understood. We focused on the regional and temporal aspects that influence biodiversity distribution. Though transportable data is rarely convenient for providing accurate images of the proportions and distribution of all components of various ecosystems, there are certain patterns and strategies that call producers will employ to obtain useful assumptions of both terrestrial and marine ecosystems. The purpose of this term paper is to conduct systematic reviews to reflect the biodiversity distribution of different spatial and temporal dimensions in the biodiversity of plant species, animal species, microorganisms, and ecosystem diversity and the factors affecting biodiversity. Biodiversity is best defined by the patterns of the world around us, and these patterns are the source for understanding biodiversity. The distribution of biodiversity is uniform and inconsistent around the world. Therefore, the shift from the equator to the poles reduced biodiversity. These show that, unlike temperate regions, the tropics have more solar energy, water availability, and a relatively constant and predictable environment. The distribution of biodiversity is affected by a variety of environmental factors, including regional geological history, environmental stability, ecosystem productivity, habitat heterogeneity and suitability, competition, and predation. Therefore, understanding the spatial and temporal distribution of biodiversity is urgently needed to develop short-term and long-term resource management strategies, and biodiversity education and training activities are innovative.